Structural and optical features of ureasiloxane-polyethylene oxide hybrids containing CeO2 nanoparticles - Truffault, L.; Magnani, M.; Hammer, P.; Santilli, C. V.; Pulcinelli, S. H. (Elsevier, 2015)
Ureasiloxane-polyethylene oxide 1900 hybrids loaded with CeO2 nanoparticles were prepared by the sol-gel method, and the effects of CeO2 incorporation on the structural and optical features of the hybrids were studied. The formation of a colloidal suspension of CeO2 nanoparticles, prepared by the sol-gel process, was monitored in situ by UV-vis spectroscopy. After separation from the colloidal suspension, the ceria powders were analyzed by transmission electron microscopy and X-ray diffraction, confirming the presence of nanoparticles about 3nm in size, containing the fluorite phase. Three different ceria concentrations were then incorporated into the ureasiloxane-polyethylene oxide hybrid. The nanostructural properties of the loaded hybrids, studied by small angle X-ray scattering, showed that the mean distance between two siloxane nodes was slightly increased by the incorporation of Ce. X-ray photoelectron spectroscopy analysis revealed the presence of both Ce(IV) and Ce(III) in the loaded hybrids. The presence of Ce significantly increased the UVA/B absorption capacity of the ureasiloxane-polyethylene oxide 1900 matrix, while maintaining its transparency in the visible region. The production of transparent UVA/B absorbing matrices loaded with CeO2-based nanoparticles extends the potential applications of U-PEO hybrids in the biomedical and optical devices fields.
Keywords: Ceria nanoparticles; Organic-inorganic hybrids; Photoprotection; Sol-gel